“And if Fiume were to Call?” The Impossible Return of Gianni Angelo Grohovaz - Eisenbichler, Konrad (Italian Canadiana)

(untitled) (Iter Press, 2021)
While most Italian emigrants can return to their hometown whenever they wish, Italians from Istria, Fiume and Dalmatia (areas that were ceded by Italy to Yugoslavia in the wake of World War Two) do not have that luxury. When they return home, they find that their hometown has changed dramatically and is no longer Italian. For them, a return “home” is, at best, a bitter return to a foreign reality and, at worst, an impossible return. By using the poetry of Gianni Angelo Grohovaz (Fiume, 1926—Little Township 1988) as a case study, this article examines Julian-Dalmatians expatriates as exiles for whom nostos is a dream and not a possibility.